BEHAVIOR OF PARENTS IN ADOLESCENTS WHO HAVE UNWANTED PREGNANCY : LITERATURE REVIEW - Ermiati Ermiati; Agfa Ramadhany Munggaran; Altia Nurrohmah; Neng Ikhtiyarotul Fikriyah; Risma Indriyani; Andinita Siti Maulidah (Journal of Maternity Care and Reproductive Health, 2021)
Unwanted Pregnancy in adolescents increases every year and raises rejection, exclusion, and even expulsion towards adolescents both by family and society. Meanwhile, adolescents who go through unwanted pregnancies need their families accompany and protect them. Objective: This literature aims to examine parents’ behavior towards adolescents who experience unwanted pregnancies. Method: Literature review using keywords in Indonesian and English. The keywords in Indonesian were "kehamilan tidak diinginkan", "orang tua", "perilaku", and "remaja". The keywords in English were "behavior”, "parents", "adolescents", and "unwanted pregnancy" searched in Google Scholar, Pubmed, Elsevier, and Proquest databases. The inclusion criteria were open access, full texts with publication years between 2010 and 2020. There were 12,212 articles collected and 10 were selected for further analysis. Findings: Positive and negative behavior from parents towards adolescents who go through unwanted pregnancies was found. Negative behavior includes shame, anger, disappointment, physical violence, and even asking for an abortion. Positive behavior includes acceptance, such as making decisions to keep the baby, taking care of the pregnancy, and providing moral and material assistance. Conclusion: Parents tend to show negative behavior when they find out about unwanted pregnancy in adolescents, but some parents show positive behavior. Recommendations: The study findings can be continued by research on interventions that can accommodate the role of parents in assisting adolescents with unwanted pregnancies.